A telephone interview version of the middle childhood HOME Observation Measurement of the Environment. (30th September 2015) - Lai, W. W.; O'Mahony, M.; Mulligan, A.
Abstract: Background: The Home Observation Measurement of the Environment (HOME) is a 59‐item observation and interview tool used to measure how suitable a child's home is for a child of his or her developmental age and has been used extensively in research. The HOME is usually performed in the child's home, which has cost implications. We wished to develop a telephone version of the HOME. Methods: We developed a 54‐item telephone interview version of the HOME and used it to measure the home environment in 77 children aged 6–10 years inclusive attending a child and adolescent mental health clinic, followed by a home visit and HOME assessment. The results of the telephone home assessment were then compared with the results of the original HOME. Results: Our sample had a mean HOME score of 47.6, standard deviation (SD) = 5.5 and a mean telephone home score of 42.6, SD = 5.1. No difference was found in comparison of the subscale mean scores of the HOME with the telephone home assessment. The agreement of 54 items in common between the HOME and telephone home assessment ranged from 73% agreement to 100% agreement. Forty‐three of 50 items had moderate to almost perfect agreement using kappa analysis (kappa = 0.41–0.99); three had 100% agreement. Conclusions: The telephone version of the HOME compares favourably with the HOME.